(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
The Aptian-Albian Scisti a Fucoidi Formation, cropping out widely in the Umbrian-Marchean Basin (Italy), consists of a varicolored pelagic sequence of thinly interbedded red and green marlstones and calcareous marlstones, dark gray to black Corg-rich calcareous shales, and light green-gray marly limestones and limestones. The variable colored lithotypes appear to be rhythmically deposited. In order to investigate in detail such rhythmicity and the mechanism leading to the accumulation of Corg-rich sediments, a core, the Piobbico core, was speciﬁcally cut through the Scisti a Fucoidi.